Effect of oral environment on contemporary orthodontic materials and its clinical implications - Madhanraj Selvaraj; Kaja Mohaideen; Karthik Sennimalai; Greeshma Shantharam Gothankar; Garima Arora (Wolters Kluwer Medknow Publications, 2023)
Contemporary orthodontics entails using advanced materials and devices, simplifying the process of tooth movement. It is well documented that orthodontic materials are subjected to various fluctuations and stresses in the oral environment, such as salivary pH, dietary habits, temperature changes, and masticatory loads. These changes reduce bonding materials' longevity, plasticize resin polymers, and reduce elastic properties. In addition, the corrosion of orthodontic appliances in the oral environment has concerned clinicians for some time. This is focused on two principal issues: whether corrosion products are absorbed into the body and cause either localized or systemic effects, and the results of corrosion on the physical properties and the clinical performance of orthodontic appliances. Recently, another major concern is the potential release of bisphenol-A from materials containing polymers such as thermoplastic aligners and resins, which is known to induce xenoestrogenicity and cytotoxicity when the tissue level exceeds the daily recommended intake. However, most of these findings are based on in vitro studies that suffer from serious drawbacks such as failure to replicate the exact oral environment and process during orthodontic treatment. Therefore, developing clinically relevant methods should be the goal of future research related to the aging of orthodontic materials. The purpose of this review is to outline the impact of the oral environment on contemporary orthodontic materials.